Inter-Clan Conflicts and the Long Journey to State-Building in Somalia – Internal and International Effects - Gemechu, Degefe Kebede (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2023)
The main purpose of the article is to investigate and analyze the inter-clan conflict and its consequences as well as the role of subregional and international organizations such as African Unions in conflict resolution and peace-building efforts in Somalia. Compared to various regions in Africa, the Horn of Africa was the region that was the most affected by internal and external conflicts. In this region, Somalia faced not only Clan problems but also suffered from rule dictatorial rules. The research hypothesis states that, traditional social structures, comprising of the clan and sub-clan identity are the main factors of disagreement and the international community peace initiatives couldn’t bring lasting peace in Somalia. Investigation questions include: What are the root causes of Somali conflict? What are the effects of the role of regional and international organizations in Somali conflict resolution? Despite being the most homogeneous nations in Africa, why did Somalis have one of the longest civil wars in the Horn of Africa? The tension in Somalia which began after the downfall of the central government in Somalia in 1991 convoluted the well-being of the citizens in the region. Among the states of the Horn of Africa, Somalia turned out to be one the most affected regarding instability and humanitarian and political turmoil. This article tries to explore the main problems Somalia faced after the end of the Cold War, the consequences of the conflict and other issues related to social and political problems taken place in Somalia. The research mainly depends on the qualitative method of data collection analysis. Głównym celem artykułu jest zbadanie i analiza konfliktu międzyklanowego i jego konsekwencji, a także roli organizacji subregionalnych i międzynarodowych, takich jak Unia Afrykańska, w rozwiązywaniu konfliktów i budowaniu pokoju w Somalii. W porównaniu z różnymi regionami Afryki, Róg Afryki był i jest regionem najbardziej dotkniętym konfliktami wewnętrznymi i zewnętrznymi. W tym regionie Somalia borykała się nie tylko z problemami klanowymi, ale także cierpiała z powodu rządów dyktatorskich. Hipoteza badawcza artykułu stwierdza, że tradycyjne struktury społeczne, na które składa się tożsamość klanowa i podklanowa, są głównymi czynnikami konfliktu, a inicjatywy pokojowe społeczności międzynarodowej nie przyniosły trwałego pokoju w Somalii. Pytania badawcze obejmują: Jakie są podstawowe przyczyny konfliktu somalijskiego? Jakie są skutki zaangażowania organizacji regionalnych i międzynarodowych w rozwiązywaniu konfliktów w Somalii? Dlaczego Somalijczycy, mimo że są najbardziej jednorodną grupą etniczną w Afryce, stoczyli jedną z najdłuższych wojen domowych w Somalii? Konflikt w Somalii, który zaczął się po upadku rządu centralnego w 1991 r., doprowadził do biedy i nędzy mieszkańców. Wśród państw Rogu Afryki Somalia okazała się jednym z najbardziej dotkniętych niestabilnością, kryzysami humanitarnymi i politycznymi. W artykule podjęto próbę zbadania głównych problemów, z jakimi borykała się Somalia po zakończeniu „zimnej wojny”, konsekwencji konfliktu oraz innych kwestii związanych z problemami społecznymi i politycznymi. Badania opierają się głównie na jakościowej metodzie analizy zbieranych danych.
Konflikty międzyklanowe i długa droga do budowania państwa w Somalii – skutki wewnętrzne i międzynarodowe
Keywords: Somalia; clan; conflict; international organization; peace process; state fragility; klan; konflikt; organizacja międzynarodowa; proces pokojowy; niestabilność państwa